Analisis Problematika Pendidikan Karakter Kejujuran di SMA Islam Samarinda - Zur’atun Khoiriyah; Marwiah Marwiah; Novita Majid (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The aim of this research is to find out the factors causing the problems of honesty Character Education at Samarinda Islamic High School, as well as the obstacles faced by schools and teachers is dealing with honesty character education problems that occur at Samarinda Islamic High School and the efforts made by schools and teachers in overcoming character education problems. Honesty at Samarinda Islamic High School. The research was conducted at Samarinda Islamic High School, using descriptive qualitative reseach subjects were the principal of the Samarinda Islamic High School, the Pancasila and Civics Education using observation, interview and documentation teachniques. The results of the research show that the problem of honesty character Education at Samarinda Islamic High School is to two casual factors, namely environmental factors and individual factors. There are internal costraints (student attitudes) and also external contraints (the role of schools and teachers) which make honesty problems difficult to minimize. Then with planning efforts. Determine the consequences for dishonest behavior and also give rewards to honesty students. Develop and supervise students so that they always behave honestly.